Butterfly politics : changing the world for women - MacKinnon, Catharine A. (The Belknap Press of Harvard University Press, 2019)
Under certain conditions, small simple actions can produce large and complex "butterfly effects." Butterfly Politics shows how Catharine A. MacKinnon turned discrimination law into an effective tool against sexual abuse--grounding and predicting the worldwide #MeToo movement--and proposes concrete steps that could have further butterfly effects on women's rights. Thirty years after she won the U.S. Supreme Court case establishing sexual harassment as illegal, this timely collection of her previously unpublished interventions on consent, rape, and the politics of gender equality captures in action the creative and transformative activism of an icon. --